2023
DOI: 10.55782/ane-2023-010
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil alleviates cerebral ischemia‑reperfusion injury by inhibiting inflammation and improving neurotrophic factor expression in rats

Abstract: The Rho kinase inhibitor fasudil exerts neuroprotective effects. We previously showed that fasudil can regulate M1/M2 microglia polarization and inhibit neuroinflammation. Here, the therapeutic effect of fasudil on cerebral ischemia‑reperfusion (I/R) injury was investigated using the middle cerebral artery occlusion and reperfusion (MCAO/R) model in Sprague‑Dawley rats. The effect of fasudil on the phenotype of microglia and neurotrophic factors in the I/R brain and its potential molecular mechanism was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Then, the activated NF‐κB is translocated into the nucleus, resulting in the transcriptional expression of genes correlated with cellular growth properties 32 . Liu et al 33 reported that elevated NF‐κB contributes to neurological injury induced by ischemia. Synthetic NF‐κB inhibitors were found to decrease infarct size in the treatment of permanent ischemia 23 …”
Section: Discussionmentioning
confidence: 99%
“…Then, the activated NF‐κB is translocated into the nucleus, resulting in the transcriptional expression of genes correlated with cellular growth properties 32 . Liu et al 33 reported that elevated NF‐κB contributes to neurological injury induced by ischemia. Synthetic NF‐κB inhibitors were found to decrease infarct size in the treatment of permanent ischemia 23 …”
Section: Discussionmentioning
confidence: 99%